Cell surface expression of membrane-anchored v-sis gene products: glycosylation is not required for cell surface transport (The Rockefeller University Press, 1986)
The v-sis gene is able to transform cells by production of a growth factor that is structurally related to platelet-derived growth factor. This growth factor has been detected in the conditioned media of v-sis transformed cells, and is able to stimulate the autophosphorylation of the platelet-derived growth factor receptor. We have used the v-sis gene product to analyze the role of protein-encoded signals in cell surface transport. We constructed several gene fusions that encode transmembrane forms of the v-sis gene product. These membrane-anchored forms of the v-sis gene product are properly folded into a native structure, as indicated by their dimerization, glycosylation, and NH2- terminal proteolytic processing. Indirect immunofluorescence demonstrated that several of these membrane-anchored gene products are transported to the cell surface. Removal of the N-linked glycosylation site from the v-sis gene product did not prevent cell surface transport. Several of these mutant genes are able to induce focus formation in NIH3T3 cells, providing further evidence that the membrane- anchored proteins are properly folded. These results demonstrate that N- linked glycosylation is not required for the cell surface transport of a protein that is in a native, biologically active conformation. These results provide a correlation between cell surface expression of the membrane-anchored v-sis gene products and transformation.